PEMBERDAYAAN MASYARAKAT DESA SUNGAI DURI II MELALUI SOSIALISASI PENGOLAHAN AIR SUNGAI MENGGUNAKAN METODE FILTERING BERJENJANG SEBAGAI SOLUSI AIR BERSIH DALAM MENGHADAPI PERUBAHAN IKLIM - Muhammad Rafani; Iin Arianti; Nurul Fitriani; Wattini Wattini; Iwan Supardi; Etty Rabihati; Rahayu Widhiastuti; Didik M Nur Haris; Irene Anggraini; Ikhwan Arief Purnama (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Sungai Duri II Village, Mempawah Regency, is facing serious challenges regarding access to clean water due to climate change, which has deteriorated river water quality. High turbidity and organic contamination have rendered river water unfit for consumption without treatment. This Community Service (PKM) activity aims to increase community independence through socialization and training on Tiered Filtering technology. The method used is Participatory Rural Appraisal (PRA) through education stages, filter assembly demonstrations, and technical assistance. The results of the activity showed a significant increase in community understanding (85%) and the availability of independent filter units at the household level. This technology is proven to reduce water turbidity visually and decrease the economic burden on residents for purchasing clean water, while also serving as a concrete adaptation step against the impacts of climate change in coastal areas. This activity successfully achieved its primary goal of socialising river water treatment using the Tiered Filtering method as a clean water solution for the people of Sungai Duri II village, as well as establishing sustainable collaboration between academics and local government/community. Questionnaire results indicated that 100% of participants stated this activity was beneficial for improving their understanding of simple yet effective clean water treatment systems. Participants expressed that the filter units are easy to use, the clean water produced is tangible, and they feel happy and satisfied with the program.